Permasalahan Matematis Siswa Kelas VIII MTsN 3 Kuningan Ditinjau dari Motivasi Belajar Siswa - Hanafiah, Dhea Khoffi; Yusritawati, Ita; Juwita, Ii; Maulina, Lina; Atilah, Ilah (Indo-MathEdu Intellectuals Journal, 2023)
The purpose of this writing is to analyze the mathematics problems of class VIII students based on student learning motivation. This research is qualitative research, namely research that presents data as a collection of words, images and not numbers. This type of research is descriptive qualitative. The subjects of this research were MTsN 3 Kuningan students in class VIII VIII 8. Interviews and questionnaires were used as tools in this research. This research data collection technique was carried out by researchers who went directly to the field. The results of the analysis of 27 students showed that students whose average score was less than 3, their answers were included in the negative answer category, namely. 6 people, while students whose average score is more than 3, the answer is. Included in the positive response category, namely 20 people and students with an average of 3 people, namely. 1 person. The conclusion of this research is that students' disinterest in learning mathematics is caused by several factors, namely students' learning difficulties which cause students to not want to answer questions asked by the teacher